Match words with deeds: Curbing water risk with the Sustainable Development Goal 6 index. (10th October 2021) - Cai, Jialiang; Zhao, Dandan; Varis, Olli
Abstract: Since the 2030 Agenda for Sustainable Development being unanimously endorsed worldwide in 2015, how to achieve sustainable water security in accordance with Sustainable Development Goal (SDG) 6 targets has become a new measure of curbing water risk. In this study, the composite SDG 6 index (SDG6I ) was developed exclusively on the basis of the SDG 6 targets for the first time. The seven SDG indicators covering five outcome-based targets were selected to systematically portray diverse water challenges (drinking water, sanitation and hygiene, wastewater treatment, water productivity, water stress, water resources management, and transboundary cooperation) for integrated water risk assessment. A quantitative spatial analysis was conducted to reveal the global implementation baseline of the SDG 6 indicators and subsequently the SDG6I by 232 countries and territories where the SDG 6 dimensions (water accessibility, water quality, water availability, and water governance) have taken the lead and fallen behind in development. First, most countries are on track to achieve universal water accessibility by 2030, yet African countries in general need to strengthen the implementation capacity of service coverage. Second, mostly only countries in Australia and New Zealand as well as Europe and Northern America are on track to achieve the targets of water quality and water availability. Third, water governance confronts the prominent challenges, both in water resources management and transboundary cooperation globally. Curbing water risk entails adequate policy measures. These measures— such as promoting socioeconomic development, improving policy effectiveness, and fostering multi-level governance and collaboration—need to be designed and implemented through nexus thinking to deliver sustainable water security. Highlights: A composite Sustainable Development Goal 6 index was developed. Most countries are on track to achieve universal water accessibility by 2030. Implementation of water quality and availability is progressing in most countries. Water governance confronts prominent challenges globally. Curbing water risk entails adequate policy measures through nexus thinking.